2004
DOI: 10.1149/1.1701870
|View full text |Cite
|
Sign up to set email alerts
|

CO-Tolerant, Sulfided Platinum Catalysts for PEMFCs

Abstract: Tolerance to small amounts of CO is important for proton exchange membrane fuel cells ͑PEMFCs͒ operating on hydrogen obtained by reforming carbon-based fuels. Platinum-based catalysts used today suffer high anode polarization losses, reducing performance and fuel efficiency. Here, findings in the search for CO-tolerant catalysts are reported. Novel platinum-based catalysts were discovered that show low polarization for oxidation of hydrogen containing 104 ppm CO, and little adsorbed CO was observed in CO strip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…It is reported that the Pt catalyst used in hydrogen fuel cells is poisoned by the traces amounts of CO ($100 ppm) in H 2 . 40 Thus, the development of an effective single-stage LT-WGS process for high-purity H 2 production is a highly desirable but challenging task, which requires innovative catalytic materials and reaction processes. Pt-based catalysts are considered promising WGS catalysts because of their high low-temperature activity, especially when Pt dispersed on metal oxides with oxygen vacancies, such as CeO 2 and doped-CeO 2 supports.…”
Section: Fts To Light Olefinsmentioning
confidence: 99%
“…It is reported that the Pt catalyst used in hydrogen fuel cells is poisoned by the traces amounts of CO ($100 ppm) in H 2 . 40 Thus, the development of an effective single-stage LT-WGS process for high-purity H 2 production is a highly desirable but challenging task, which requires innovative catalytic materials and reaction processes. Pt-based catalysts are considered promising WGS catalysts because of their high low-temperature activity, especially when Pt dispersed on metal oxides with oxygen vacancies, such as CeO 2 and doped-CeO 2 supports.…”
Section: Fts To Light Olefinsmentioning
confidence: 99%
“…11 From the aspect of practical applications in the hydrogen fuel cells, catalysts for the WGS reaction with low working temperature, especially under 200 1C, are highly desirable because the low temperature can maintain low levels of CO so that the platinum electrode of hydrogen fuel cells is not poisoned. 12 Front runner catalysts in low-temperature WGS reactions are noble metals supported on reducible oxide substrates and alkali-promoted noble metals. 13,14 A remarkable breakthrough has been achieved in a recent experiment, in which the CO conversion employing a-MoC-supported Au layered clusters as a catalyst is at least one order of magnitude higher (close to 98% at 423 K) 15 than other known catalysts at the same temperature.…”
Section: Introductionmentioning
confidence: 99%
“…1) so as not to affect the downstream applications 13 . As an example, a trace amount of CO (around 100 ppm) in H 2 will seriously poison the Pt-based catalyst on the anode of proton exchange membrane fuel cell and reduce the performance significantly 14 . Therefore, the direct production of high purity hydrogen under mild conditions is more economical and eco-friendly but a challenging task, which requires innovative catalytic processes.
Fig.
…”
Section: Introductionmentioning
confidence: 99%